47.0k views
0 votes
Write the difference of the given functions (f - g)(x):
f(x) = x² + 2x - 6 and g(x) = x + 5.

User Karudi
by
5.0k points

1 Answer

3 votes

Answer:

(f - g)(x) = x² + x - 11

General Formulas and Concepts:

Pre-Algebra

  • Properties

Algebra I

  • Combining like terms

Explanation:

Step 1: Define

f(x) = x² + 2x - 6

g(x) = x + 5

(f - g)(x) is f(x) - g(x)

Step 2: Find

  1. Substitute: (f - g)(x) = x² + 2x - 6 - (x + 5)
  2. Distribute -1: (f - g)(x) = x² + 2x - 6 - x - 5
  3. Combine like terms: (f - g)(x) = x² + x - 11
User Arne Lund
by
5.0k points